Anatomical Characterization and Protein Profiles in Adventitious and Storage Roots of Two Commercial Thai Cassava Varieties - Siriporn Wechkrajang; Vichan Vichukit; Prachumporn Toonkool; Sutkhet Nakasathien (Agriculture and Natural Resources, 2006)
Anatomical changes and protein expression patterns were examined in adventitious and storage roots of two commercial varieties of cassava grown in Thailand, namely Rayong 1 (R1) and Kasetsart 50 (KU50). Both storage and adventitious roots were harvested consecutively every 7 days after planting for a period of 9 weeks. Adventitious and storage roots were collected separately, cross-sectioned to observe anatomical changes under light microscopy. Iodine-stain, indicating starch accumulation revealed that starch accumulation started 35 days after planting in both varieties. Total protein in adventitious and storage roots were extracted in ice-cold saline buffer and analyzed for protein profile using SDSPAGE. Similar to the anatomical changes, SDS-PAGE revealed unique protein bands in the cassava roots from 35 days after planting onward. Further analysis will be carried out to investigate and differentiate the unique protein patterns between adventitious roots and storage roots using 2-dimensional gel electrophoresis technique.